ESSENTIAL AMENITIES IN ANAMBRA STATE POLYTECHNIC MGBAKWU; ITS IMPLICATION ON STAFF AND STUDENTS ATTITUDES, PERFORMANCES AND EDUCATIONAL DEVELOPMENT - O.M, Onoura; C.I, Chigbo.; I.M, Ibekwe; A.C, Okoye. (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2023)
The study looks at the availability of basic amenities in Nigeria higher institutions of learning and the implication on students’ attitudes and academic performances. Primary data were collected and the data collected from the respondents was analyzed using chi-square test, exploratory data analysis and Pearson’s chi-squared test. The result of the findings revealed that electricity, transportation, water supply, information and communication technology, and lecture theatres have significant influence on the performance of students in Higher institutions in Nigeria.